Il simbolico e la via del movimento delle donne (Materiali di Estetica. Terza serie, 2022)
Symbolic politics has been one of the key phrases in Italian feminism since the 1970s. This text describes the historical origins and significance of this concept together with the difference in the use of the symbolic dimension in traditional male politics. The most important difference is that female politics are born from living and affective relations which cannot be permanently established and rotate around non-formalized procedural practices. The sense that emerges is felt during the actual process and the symbolic is therefore experienced and transformed from the inside with the authority that comes from these practices, which influence and modify each other due to their closeness. They spread by proximity.
Keywords: Symbolic politics; Italian Feminism; The Sexual Difference; Practices